Lexicostatistics of Toba Language, Sibolga Language, and Minangkabau Language - Rezky Khoirina Tarihoran; Dwi Widayati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study examines the Toba Batak language, the Sibolga Coastal language, and the Minangkabau language belonging to the Austronesian or Polynesian Malay family. The assumption regarding the kinship of the three languages is in the fact that there are similarities and similarities in form and meaning which are a reflection of the same historical heritage which is thought to have come from the mixing of natives with immigrants. This research uses the lexicostatistical method. The first stage, collects 200 basic vocabulary compiled by Morris Swades. The method used in providing this data is the referential method, while the technique used is the note-taking technique. Second, determine the pairs which of the three languages is a cognate language. Third, calculate the age and separation time of the three languages. Fourth, calculate the error term to determine a more precise separation time. From this research, it was found that the language status of the Sibolga language and the Minangkabau language is a family category, while the language status of the Minangkabau - Toba Batak and Sibolga - Toba Batak languages is a stock category.